Changes in the nickel hydroxide properties under the influence of thermal field in situ and ex situ during electrochemical synthesis - Kovalenko, Vadym; Kotok, Valerii (Eastern-European Journal of Enterprise Technologies, 2020)
Nickel hydroxide is widely used in supercapacitors, alkaline batteries, for the electrocatalytic oxidation of organic contaminants, etc. Due to their electrochemical activity, Ni(OH)2 (α+β) samples of a layer structure synthesized in a slit diaphragm electrolyzer are the most promising. The effect of the thermal field on the structural characteristics of layered (α+β) Ni(OH)2 was studied. The effect was assessed in two ways: 1) internal (in situ) cooling directly in the electrolyzer by cooling the cathode from the rear side; 2) external (ex situ) heating directly after the electrolyzer when passing through a spiral heat exchanger heated to 90 °C. The crystal structure of the samples was studied by X-ray phase analysis. It was shown that the base sample obtained without changing the thermal field was a monophase layered (α+β) structure with a high content of α-modification and a gradient transition from α to β through a number of intermediate structures. The crystallinity of the sample was not high. During the internal cooling of the cathode, the crystallinity decreased and the fraction of the α-modification increased. External heating of the nickel hydroxide suspension immediately after leaving the electrolyzer led to the recrystallization of the samples with the decomposition of the (α+β) layered structure and formation of β-Ni(OH)2 with high crystallinity. It was found that external 6-minute heating did not change the crystal structure. This is explained by the fact that the aging process of nickel hydroxide at an elevated temperature is a crystal-chemical transformation, which is characterized by an induction period, during which the rate of the process is minimal. As a result, the study has shown the possibility of controlling the type of forming crystalline modification of nickel hydroxide and its crystallinity by changing the internal (in situ) or external (ex situ) thermal field